Perancangan Website Jasa Pembuatan Kebun Melon Dengan Menggunakan Metode Prototype - Septian Angga Maulana; Sri Widiyati; Tinuk Agustin (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
In running a business in the service sector, it is necessary to have media that can be used to introduce their business in the mass media. One of the mass media that is suitable in this era is the website. The website that will be designed will contain testimonials, services offered and articles that can help users. In offering services through the website, because the services of making melon gardens are still common in the community. So that the existence of this website can create new jobs and can make it easier for service users. The method used in making this information system is to use a prototype model, where the flow and stages used include identifying users and developing prototypes. The results of this study are in the form of an information system in the form of a website that offers services for making melon gardens.